The Catholic Church on Marital Intercourse: From St. Paul to Pope John Paul II - Obach, Robert (Lexington Books, 2008)
The Catholic Church on Marital Intercourse traces the development of the Church's theology of marital sexuality from New Testament times to the present day. The early ecclesial leaders promoted a theology of sexuality based on Stoicism's biological perception that sexual activity was solely for the purpose of reproduction. Only in the early twentieth century did a few theologians begin to move beyond discussing 'the purposes of marital intercourse' to discussing the meaning that the marital act might have for the spouses themselves. With the Second Vatican Council (1962-1965), a new and positive view of marital sexuality emerged recognizing the Pauline view that the couple's marital acts express their love for each other along the lines of Christ's love for his church (Ephesians 5). In sum, The Catholic Church on Marital Intercourse treats the way in which the Catholic Church has moved away from an attitude of conditional acceptance of marital intercourse on the basis of its utility to recognition that the dynamics of sexual union are both good and holy, not only because that is the way children are conceived, but also because the marital act enhances the love of husband and wife for each other.